Defoliation tolerance of soybean cultivars commercially released in different decades Tolerancia a la defoliación de cultivares de soya liberados para su comercialización en diferentes décadas - Turek T.L.* (2023)
© 2023, Universidad Nacional de Colombia. All rights reserved.Breeding programs have increased the precocity and yield poten-tial of modern soybean cultivars. Such changes may have altered the crop tolerance to defoliation due to the smaller leaf area of modern cultivars. The objective of this study was to determine the tolerance to defoliation of soybean cultivars commercialized in Brazil in different decades, their photosynthetic efficiency and the relationship between photosynthetic efficiency and tolerance to defoliation in the reproductive phase. The experiment was set in a greenhouse with controlled humidity and temperature, in the municipality of Lages, Santa Catarina State, South of Brazil, during the growing season of 2018/2019. A randomized block design was used, with treatments arranged in a 5×5 factorial scheme. The first factor was composed of five soybean cultivars released in different years: Davis (1968), Paraná (1974), BR-16 (1985), FT Abyara (1991), and Brasmax Elite IPRO (2014). The second factor consisted of five levels of defoliation applied in stage R3: 0, 16.6, 33.3, 50.0, and 66.6%. Leaf area, photosynthetic activity parameters, grain yield and its components were deter-mined. Brasmax Elite IPRO had the lowest grain yield per plant and did not increase yield compared to older cultivars, regard-less of defoliation level. There were no significant differences in photosynthetic efficiency or defoliation tolerance between the modern cultivar Brasmax Elite IPRO and the old cultivars Davis, Paraná, BR-16, and FT Abyara.